Pengembangan e-Comic Matematika Berbasis Pendekatan Matematika Realistik (PMR) pada Materi Persamaan Linear Satu Variabel - Yuniawati, Sinta; Palupi, Evangelista Lus Windyana; Fiangga, Shofan (Universitas Negeri Surabaya, 2024)
E-comic mathematics is a comic-shaped learning supplement whose creation and use process utilizes technological media. The use of e-comic as a learning supplement is intended to assist students in learning the concept of a mathematical material independently outside of classroom learning activities. Realistic mathematics approach (PMR) is a learning theory in mathematics education that connects mathematics with real life and human activities. Linear equation of one variable (PLSV) is a mathematics material in grade VII. The definition of PLSV is an equation that has only one variable with the highest rank of degree one. This study aims to describe the process and results of the development of PMR-based math e-comic on PLSV material which is measured through aspects of validity, practicality, and effectiveness. The subjects in this study were seventh grade students who had received algebraic arithmetic operation material. This research is a development research using ADDIE development model with five phases namely analysis, design, development, implementation, and evaluation. Data collection methods in this study are: validation by experts, one-to-one trials, and field tests. The results showed that the math e-comic met the criteria of being very valid with an average percentage value from the validator of 91.15%. The results of the user response questionnaire in the field test showed an average percentage value of 82.5% and met the practical criteria. In addition, there was an increase in student learning outcomes in the pretest and post-test indicated by the acquisition of an N-Gain value of 0.7 with a moderate upper limit category during the field test, thus meeting the effective criteria. Based on the evaluation results, it shows that the PMR-based math e-comic on PLSV material developed has met the valid, practical, and effective criteria.